Effect of inside heated cylinder on the natural convection heat transfer of nanofluids in a wavy-wall enclosure. (December 2016) - Hatami, M.; Safari, H.
Highlights: Natural convection heat transfer of nanofluids in a wavy-wall enclosure is studied. Finite element method (FEM) has been employed to solve the governing equations. A heated cylinder is located in the cavity. Effects of center location for cylinder on the Nusselt numbers are investigated. Abstract: In this study, natural convection heat transfer of nanofluids in a wavy-wall enclosure is studied while a heated cylinder is located inside the cavity. The governing equations for a simple cavity are studied based on the previous work and changed it to complicated two-phase nanofluid and solved by finite element method (FEM). Because the location on inside cylinder has a significant effect on the heat transfer and Nusselt number, it is important to find the best location for this cylinder. In our study the cylinder is movable in X and Y directions which affects the temperatures, stream lines and nanoparticles concentration contours. The results indicate that center location for the cylinder assists the heat transfer in both wavy side walls.